Accelerating food production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Mellor, J.W et al (eds.), 1987. Accelerating Food Production in sub-Saharan Africa. John Hopkins University Press, Baltimore and London, 417 pp. (UKL 31.05)